Compensatory synaptotagmin-11 expression conceals parkinson’s disease-like phenotypes in parkin knockout mice - Nan Dong; Zhenli Xie; Anqi Wei; Yuxin Yang; Yongning Deng; Xu Cheng; Bianbian Wang; Yang Chen; Yuhao Gu; Jingyu Yao; Yuhao Qin; Chaowen Zheng; et al. (Cell Communication and Signaling, 2025)
Abstract Animal models are crucial for elucidating the pathological mechanisms underlying Parkinson’s disease (PD). Unfortunately, most of transgenic mouse models fail to manifest pathological changes observed in PD patients, pending the advancement of PD research. However, the mechanism underlying this discrepancy remains elusive. Here, we provide compelling evidence that the compensatory expression of synaptotagmin-11 (Syt11) plays a key role in concealing PD-associated phenotypes in parkin knockout (KO) mouse models. Unlike the normal dopamine (DA) release and motor behaviors observed in parkin KO mice, parkin knockdown (KD) in the substantia nigra pars compacta (SNpc) in adult mice led to both the impaired DA release and the pronounced motor deficits. Interestingly, Syt11, a well-established parkin substrate involved in PD, was specifically upregulated in parkin KD mice and in parkin KO mice during the suckling stage, but not in adult parkin KO mice. Importantly, the overexpression of Syt11 alone is capable of inducing PD-like motor and non-motor impairments, as well as the impaired DA release and reuptake, which is essential for parkin-associated pathogenesis of PD. Therefore, this work not only elucidate a compensatory mechanism that accounts for the absence of overt PD phenotypes in parkin KO mice, but also contribute to the comprehensive understanding of the progression of PD, opening new avenues for the therapeutic treatment of PD.